Palpable migratory arciform erythema - does this entity really exist? - Szepietowski, Jacek C. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2004)
Palpable migratory arciform erythema has rarely been reported in medical literature. A 59-year old female patient was referred to our department because of slightly itchy, erythematous lesions on the back, which had been present for the previous 4 years. Previously she had been treated with topicalcorticosteroids without any improvement. Within the 4-year period the lesions had shown a partly spontaneous resolution with the formation of new arciform or semiannular lesions. On admission she presented with 2 elevated and firmly palpable erythematous patches on the back. The lesions had sharp and distinct margins, about 4 cm in diameter, and an annular shape with a tendency towards central clearing. Histological examination revealed dense lymphocytic infiltrate located around the epithelial structures of the adnexa and around the blood vessels. Immunohistochemistry showed predominantly T cells (CD34-positive, CD45 RO-positive cells). A diagnosis of palpable migratory arciform erythema was established and the patient was treated with oral tetracycline and topical corticosteroids. This treatment resulted in marked improvement within 7-10 days.
Keywords: Antigeni, CD20; Antigeni, CD45; Antigens, Cd20; Antigens, Cd45; dermatologija; Diagnosis; Drug Therapy; Eritem; Erythema; Immunohistochemistry; Imunohistokemija; Kožne bolezni; Limfociti T; Middle Age; Pathology; Pseudolymphoma; Psevdolimfom; Skin Diseases; Srednja leta; T-Lymphocytes